Ethics of war and peace in Iran and Shiʻi Islam - Mahallati, Mohammad Jafar Amir, 1952- (University of Toronto Press, 2016)
"Nearly four decades after a revolution, experiencing one of the longest wars in contemporary history, facing political and ideological threats by regional radicals such as ISIS and the Taliban, and having succeeded in negotiations with six world powers over her nuclear program, Iran appears as an experienced Muslim country seeking to build bridges with its Sunni neighbours as well as with the West. "Ethics of War and Peace in Iran and Shi'i Islam explores the wide spectrum of theoretical approaches and practical attitudes concerning the justifications, causes and conduct of war in Iranian-Shi'i culture. By examining primary and secondary sources, and investigating longer lasting factors and questions over circumstantial ones, Mohammad Jafar Amir Mahallati seeks to understand modern Iranian responses to war and peace. His work is the first in its field to look into the ethics of war and peace in Iran and Shi'i Islam. It provides a prism through which the binary source of the Iranian national and religious identity informs Iranian responses to modernity. By doing so, the author reveals that a civilization-conscious soul in modern Iran is re-emerging"--Provided by the publisher